Mengembangkan Kurikulum Mata Pelajaran Agama Di MI/SD - Annisa At Thohiroh; Fitri Khairani Pardede; Fikriah Amanda; Zunidar Zunidar (CV. SINAR HOWUHOWU, 2026)
The development of the religious education curriculum in Madrasah Ibtidaiyah (MI) and Elementary Schools (SD) is a strategic effort to achieve educational goals focused on fostering students who are faithful, pious, and possess noble character. This study aims to describe the nature and characteristics of religious education subjects in MI/SD, analyze the foundations of curriculum development, and examine the components that support the development of the religious education curriculum. The study employs a library research method with a qualitative descriptive approach. Data were collected from various literature sources, including books, scientific journals, and academic documents relevant to religious education curriculum development. Data analysis was conducted using content analysis techniques through the processes of data collection, reduction, presentation, and conclusion drawing. The findings indicate that religious education subjects encompass cognitive, affective, and psychomotor aspects, thereby playing a significant role in character formation among students. The development of the religious education curriculum is based on philosophical, psychological, sociological, and religious foundations that complement one another in supporting the achievement of educational objectives. Furthermore, the components of objectives, content, learning strategies, and assessment serve as the main elements determining the successful implementation of the curriculum. Through appropriate curriculum development, religious education in MI/SD is expected to produce students who possess strong religious competencies, good character, and the ability to face the challenges of life in the modern era.